Childhood myelodysplastic syndrome with increased fibrosis in association with neurofibromatosis 1: A case report - Katoch, Nandita; Soni, Arun; Gautam, Piyush; Kaul, Rashmi; Chander, Bal (Indian Journal of Case Reports, 2024)
Childhood myelodysplastic syndromes (MDSs) are rarely seen and their association with neurofibromatosis 1 (NF1) is also rare. Monosomy 7 predisposition syndrome can arise in NF1 patients. MDS with increased fibrosis carries a poor prognosis. We are reporting the case of a 7-year-old boy who presented with fever and on routine evaluation, pancytopenia was found. He had multiple café-au-lait spots. Further testing revealed dysplastic megakaryocytes along with increased marrow fibrosis. This case contributes further to the knowledge of childhood MDS and NF1.